Determinants of success and longevity of nascent enterprises: a literature review of explanatory factors - Souissi, Mourad (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2025)
The success and longevity of nascent enterprises remain major challenges in the field of entrepreneurship. Although entrepreneurship is increasingly seen as a driver of economic development and innovation, a significant proportion of newly-created small and medium-sized enterprises (SMEs) fail in their first years of operation. This study synthesizes the main determinants influencing the survival and performance of emerging firms, drawing on theoretical frameworks such as resource theory and environmental contingency theory. Our results highlight the decisive role of individual entrepreneurial characteristics, access to financial, human and social resources, and the impact of the economic and regulatory environment on firm viability. Furthermore, this research highlights the importance of strategic adaptability, managerial skills and institutional support in reducing the risk of entrepreneurial failure. Based on these findings, we make recommendations for policymakers and practitioners to strengthen SME resilience. Future research should delve deeper into sectoral variations in business survival and examine the impact of digital transformation on their sustainability.